Formation of military position in the valuable system of cadets - Maksim V. Sysolyatin (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The article presents a brief theoretical review of existing scientific papers that address the problems of social and professional identity, value orientations, as well as studying the relationship of these psychological concepts in the context of the formation of social identity of an individual.It also presents the results of the conducted empirical research, in particular, a comparative analysis of the significance of values for cadets of higher military educational institutions at various stages of military-professional socialization, the dynamics of the integrated structure of their value orientations in each course are examined, and the dependence of military social identity on terminal and instrumental values. The sample of the study was 255 people, men, the average length of military service for 3.1 years.The cadets' value orientations were revealed using M. Rokich's “Value Orientations” questionnaire, the characteristics of military identity were determined using the average of four scales of military social identity from the identity questionnaire developed by us based on the questionnaire.The correlation and regression analysis, as well as the arithmetic average calculation of the values for each course, made it possible to identify the conformity of the officer’s ideas about the personality with the value orientations that are formed in the process of military-school education, the diachronic nature of the integration of the structure of value orientations at each of the military-professional stages socialization, as well as the formation of the internal value structure of the personality of the cadet as a future commander. The results obtained can be used by personnel agencies to prepare recommendations for the commanders of units on the formation of the value system of subordinates.